2000
DOI: 10.1007/s004210050051
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of endurance training in elderly people over a short period is reversible

Abstract: The present study assessed daily activity, physical capacity and body composition in 11 initially sedentary healthy subjects [5 men and 6 women, mean age 62.8 (SD 2.7) years] before training (T(o)), after completion of 7 (T(7w)) and 14 (T(14w)) weeks of training, and again 6 (T(6m)) and 12 (T(12m)) months after training. The mean daily activity index decreased from T(7w) to T(12m) reaching a lower level than at T(o) [T(12m) - T(o) = -1.5 (SD 4.6) units, P = 0.18]. Mean maximal oxygen uptake (VO(2max)) and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
(58 reference statements)
1
4
0
Order By: Relevance
“…Overweight/obesity was highest among individuals aged 55–64 years but declined at ages 65+ years. This finding corroborates data from large scale surveys41–44 which show that mean body weight and BMI gradually increases during most of adult life and reach peak values at 50–59 years of age in both men and women and after the age of 60 years, mean body weight and BMI tend to decrease 33 45 46. Similarly in South Africa it was found that overweight/obesity tends to increase with age 21…”
Section: Discussionsupporting
confidence: 88%
“…Overweight/obesity was highest among individuals aged 55–64 years but declined at ages 65+ years. This finding corroborates data from large scale surveys41–44 which show that mean body weight and BMI gradually increases during most of adult life and reach peak values at 50–59 years of age in both men and women and after the age of 60 years, mean body weight and BMI tend to decrease 33 45 46. Similarly in South Africa it was found that overweight/obesity tends to increase with age 21…”
Section: Discussionsupporting
confidence: 88%
“…The results of the present study suggest that high-intensity endurance exercise may be beneficial, both prophylactically and to promote health. Because the benefit of endurance training in elderly people over a short period is reversible (Morio et al, 2000), one should consider increasing endurance training intensity to maintain enhanced cardiorespiratory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the years, many studies have demonstrated an age-related decline in cardiorespiratory function, as exemplified by the body's maximum capacity to utilize oxygen (VO 2max ) (Morio et al, 2000;Wilmore & Costill, 1994). Endurance training could reverse this decline in aerobic capacity in older individuals.…”
mentioning
confidence: 99%
“…Others have demonstrated that the decrease in aerobic capacity, loss of muscle and gain of fat can be reversed in elderly people by endurance training (Denis, Chatard, Dormois, Linossier, Geyssant, Lacour, 1986). However, for the favourable effects of the training to be maintained, it is necessary to maintain the training (Morio et al, 2000). Thus a regular level of exercise should be maintained throughout life.…”
Section: Discussionmentioning
confidence: 99%